Deceptive Presentation of Low-Grade Lymphoma with Grade 3 Marrow Fibrosis and Aplasia: Diagnostic and Clinical Considerations - Singh, Suvir; Sharma, Rintu; Singh, Jagdeep; Paul, Preethi (Indian Journal of Medical and Paediatric Oncology, 2023)
Bone marrow fibrosis with lymphoproliferative disorders is rare with the exception of hairy cell leukemia and nodular sclerosis Hodgkin's lymphoma. We report the case of a 63-year-old gentleman with indolent B-cell lymphoma presenting with myelofibrosis and aplasia. He was evaluated for pancytopenia with no organomegaly or lymphadenopathy. Bone marrow aspiration was a dry tap and biopsy revealed a hypocellular marrow with a cellularity of 10 to 20% with absent megakaryocytes and grade 2 to 3 reticulin fibrosis. Myeloproliferative neoplasms were ruled out based on morphology and absence of myeloid mutations on next-generation sequencing. Further sections revealed interstitial infiltrates of lymphoid cells with round, clumped chromatin and inconspicuous nucleoli, which on immunohistochemistry (IHC) were positive for CD20 and BCL2, and negative for CD5, CD10, BCL6, annexin A1, cyclin D1, and TdT. The final diagnosis was thus confirmed as CD5-negative low-grade B-cell lymphoma and he was initiated on therapy with a combination of Bendamustine and Rituximab. He had resolution of symptoms and cytopenia after six cycles of the same. Presence of significant myelofibrosis on the background of a hypocellular marrow can mimic several subtypes of myeloproliferative neoplasms or myelodysplastic syndromes, providing a diagnostic challenge. IHC is essential in determining the exact subtype to decide further therapy. Based on literature search, only a handful of patients with this presentation have been described and this case will be a valuable addition to the same.
Keywords: lymphoma; histopathology; fibrosis; diagnosis; pathology; biopsy; cancer; immunohistochemistry